2020
DOI: 10.1094/phyto-07-19-0260-fi
|View full text |Cite
|
Sign up to set email alerts
|

Barley yellow dwarf virus Can Be Inoculated During Brief Intracellular Punctures in Phloem Cells Before the Sieve Element Continuous Salivation Phase

Abstract: The distinguished intracellular stylet puncture called phloem-pd (potential drop [pd]) produced by Myzus persicae has been associated with the transmission of the semipersistently transmitted, phloem-limited Beet yellows virus (BYV, Closterovirus). However, the production of intracellular punctures in phloem cells (phloem-pd) by other aphid species and their role in the transmission of persistently transmitted, phloem-limited viruses are still unknown. Previous studies revealed that inoculation of the persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Ultrastructural analyses with the biological model M. persicae on sugar beet clearly demonstrated that phloempds were associated with stylet penetrations in sieve elements or companion cells whereas other cells (mesophyll, bundle sheath cells and possibly phloem parenchyma) are penetrated during standard-pds [49]. The phloem-pds were shown to play an important role in inoculation of the semi-persistent phloem-limited beet yellows virus (BYV) by M. persicae and the persistently transmitted, phloem-limited BYDV by Rhopalosiphum padi (Linnaeus, 1758) [48,50]. Long stylet penetration (i.e.…”
Section: Epg Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructural analyses with the biological model M. persicae on sugar beet clearly demonstrated that phloempds were associated with stylet penetrations in sieve elements or companion cells whereas other cells (mesophyll, bundle sheath cells and possibly phloem parenchyma) are penetrated during standard-pds [49]. The phloem-pds were shown to play an important role in inoculation of the semi-persistent phloem-limited beet yellows virus (BYV) by M. persicae and the persistently transmitted, phloem-limited BYDV by Rhopalosiphum padi (Linnaeus, 1758) [48,50]. Long stylet penetration (i.e.…”
Section: Epg Systemmentioning
confidence: 99%
“…several tens of seconds to several hours) in sieve elements that eventually attain phloem sap ingestion always begins by the stereotypical E1 waveform. It is related to salivation and described as the essential phase for inoculation of persistently or semi-persistently transmitted plant viruses by aphids [14,50], whiteflies [51] or leafhoppers [52]. The E1 waveform is usually followed by a short transition period before the E2 waveform.…”
Section: Epg Systemmentioning
confidence: 99%
“…Late in the intracellular puncture, sub‐phase II‐3 takes up fluid that conveys virions to the acrostyle, causing acquisition. Early in the intracellular puncture, sub‐phase II‐1 represents salivation (or perhaps egestion 70 ), which dislodges viruses from the acrostyle and out the stylet tips, causing inoculation into the phloem cell 72 . Persistent‐circulative viruses are acquired during ingestion from phloem sieve elements (represented by waveform E2 by aphids, psyllids, and whiteflies) 72,73 .…”
Section: Perspectives For Pest Managementmentioning
confidence: 99%
“…Some viruses are nonpersistent and stylet-borne, meaning they remain in the vector for only a short time after acquisition, and are carried on a specific binding area, the acrostyle, at the stylet tips. 68 Acquisition and inoculation have been correlated with specific sub-phases of the potential drop (intracellular puncture) waveform, 69 or in certain species, a special type of potential drop (or pd), the phloem-pd, which represents penetration of a phloem sieve element or companion cell; 70,71 both types of intracellular punctures last only a few seconds. Late in the intracellular puncture, sub-phase II-3 takes up fluid that conveys virions to the acrostyle, causing acquisition.…”
Section: Feeding Damage and Pathogen Transmission By Hemipteransmentioning
confidence: 99%
“…The probing and feeding behavior of piercing and sucking insects can be monitored using the EPG technique [ 15 ], which is a useful tool to investigate insect-plant interactions, including the localization and characterization of host-plant resistance to aphids [ 16 , 17 , 18 , 19 ]. Furthermore, EPG allows to understand the transmission mechanisms of plant pathogens by their insect vectors [ 11 , 20 , 21 , 22 , 23 ] and to study the mode of action of insecticides [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%